In-Plane Stiffness of Cross-Laminated Timber Panels with Openings. Issue 2 (1st May 2017) - Shahnewaz, Ida; Tannert, Thomas; Shahria Alam, M.; Popovski, Marjan
Abstract: Cross-laminated timber (CLT) is increasingly being used in residential and nonresidential applications. While the quantification of the in-plane stiffness of CLT shear walls is required to design a CLT structure subjected to lateral loads, the design guidance, specifically for walls with openings, is limited. The study quantified the stiffness of CLT panels under in-plane loading. A finite element analysis model of CLT panels was developed and verified with test results of CLT panels under in-plane loading. The influence of openings on the stiffness was evaluated using a parametric study varying the size and shape of the openings and the aspect ratios of the openings as well as the wall aspect ratios. Based on the results, equations were proposed to calculate the in-plane stiffness of CLT walls with openings. Subsequently, a sensitivity analysis was performed to evaluate the contribution of each parameter to the model response.